Examining the influence of settlement morphology and separation zones policies on the availability of shallow coal resources in the United Kingdom. (December 2017) - Bee, Emma J.; Mankelow, Joseph M.
Abstract: In 2013, demand for coal in the UK was 60 million tonnes. Of this, 12.7 million tonnes (21%) came from indigenous sources; the majority of which was from surface mining (8.6 million tonnes). Many planning applications for surface mining of coal and the coal extraction that follows, are often a source of conflict with the communities who live within shallow coalfield areas. Policies which enforce a gap, or 'separation zone', between communities and surface coal mining operations exist in Wales and Scotland, but do not exist in England. This paper examines the effect of applying separation zones on the availability of shallow coal resources within two study areas; one within the South Wales Coalfield, the other within the Midlands Coalfield (comprising the Yorkshire, Nottinghamshire and North Derbyshire Coalfield areas). Density profiles and a shape-index algorithm are used to compare and contrast settlement morphology (i.e. shape or footprint) and distribution to determine whether they have a bearing on the areal extent of any potential separation zone applied. The implications on the availability of shallow coal resources of applying different separation zone distances around settlements within these two areas are explored. Results reveal that although the settlement morphology is important in determining the area of the separation zone, and has greatest influence in the South Wales Coalfield, the area of coal resource sterilised by the application of separation zones is greatest in the Midlands Coalfield due to it having a higher proportion of urban development situated on the surface extent of the shallow coal resource. Highlights: The shape of a settlement can affect the area of a separation zone. Elongated settlements have a greater influence on the area of separation. Settlement shape has the potential to influence the surface area of shallow coal resource sterilised. Results can help inform policy development in the UK and abroad.